Analisis Madzhab Syaf’i Dan Hanafi Tentang Batasan Usia Perkawinan - Hanifah, Abu; Nasa, Raihan; Hafiz, Maulan Abdul (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2025)
Determining the age limit for marriage is an important issue in Islamic law because it is closely related to the physical, mental, and social maturity of the prospective bride and groom. This article examines a comparison of the views of the Shafi'i and Hanafi schools of thought particularly the opinion of Imam Abu Hanifah regarding the age of puberty as a condition for a valid marriage contract. The research method used is normative research with a juridical-empirical approach through a literature study of classical fiqh literature and positive legal regulations in Indonesia. The results of the study show that the Shafi'i school of thought sets the maximum age of puberty at 15 years for both males and females, while Imam Abu Hanifah sets it at 18 years for males and 17 years for females. Although both agree that the validity of marriage is not only determined by age, but also by the attainment of puberty and the ability to bear household responsibilities, the modern context demands the strengthening of legal protection for children through restrictions on the minimum age of marriage. Based on an analysis of maqāṣid al-syarī‘ah, Imam Shafi'i's opinion, which focuses on puberty as an indicator of maturity with adjustments to health and psychological standards is considered the most valid to be integrated into the contemporary family law system.Keywords: Minimum Age for Marriage, Islamic Law, Shafi'i School of Thought, Hanafi School of Thought, Maqasid al-Shari'ah Abstrak:Penentuan batas usia perkawinan merupakan isu penting dalam hukum Islam karena berkaitan erat dengan kematangan fisik, mental, dan sosial calon mempelai. Artikel ini mengkaji perbandingan pandangan Mazhab Syafi’i dan Mazhab Hanafi khususnya pendapat Imam Abu Hanifah mengenai batas usia baligh sebagai syarat sahnya akad nikah. Metode penelitian yang digunakan adalah penelitian normatif dengan pendekatan yuridis-empiris melalui studi pustaka terhadap literatur fikih klasik dan regulasi hukum positif di Indonesia. Hasil kajian menunjukkan bahwa Mazhab Syafi’i menetapkan usia baligh maksimal 15 tahun bagi laki-laki dan perempuan, sedangkan Imam Abu Hanifah menetapkan 18 tahun bagi laki-laki dan 17 tahun bagi perempuan. Meskipun keduanya sepakat bahwa syarat sah nikah tidak hanya ditentukan oleh usia, melainkan pada tercapainya baligh dan kemampuan memikul tanggung jawab rumah tangga, konteks modern menuntut penguatan perlindungan hukum bagi anak melalui pembatasan usia minimal perkawinan. Berdasarkan analisis maqāṣid al-syarī‘ah, pendapat Imam Syafi’i yang berfokus pada baligh sebagai indikator kematangan—dengan penyesuaian terhadap standar kesehatan dan psikologis—dinilai paling rajih untuk diintegrasikan dalam sistem hukum keluarga kontemporer.Kata Kunci: Batas Usia Perkawinan, Hukum Islam, Mazhab Syafi’I, Mazhab Hanafi, Maqāṣid al-Syarī‘ah